Determination of Boron Concentration at Sausage Samples with Distillation of Ester Borane Method using Fluorescence Spectrophotometry - Aisyiah Restutiningsih Putri Utami; Micha Mahardika; Lailatusholihah, Isna (KOVALEN: Jurnal Riset Kimia, 2023)
The study of borax contamination in food samples was successfully analyzed. This study used sausage samples using the Fluorescence Spectrophotometry method. Sausage samples were from Daerah Istimewa Yogyakarta (DIY). This study used 4 sausage samples. The samples were given labels A, B, C, and D. The steps of the research were optimation of distillation time, optimation of catalyst, optimation of solvent, and then followed by analyzing the borax concentration on sausage samples. Based on this study, the optimum distillation time was 24 hours. On the other hand, the best catalysts and solvents were sulphuric acid and ethanol. The A and B samples contained borax contamination and the concentration was under 5 ppm. The C and D samples contained borax contamination and the concentration was above 5 ppm. The conclusions were that A and B samples were not given borax addition and C and D samples were given borax addition.